Будинок полкової канцелярії в Чернігові у кінці ХІХ ст. - Доценко, А. (Сiверянський лiтопис, 2015)
У статті мовою документів Державного архіву Чернігівської області висвітлюється сторінка історії будинку полкової канцелярії і його стан на кінець ХІХ ст. у зв’язку з передачею Чернігівському губернському земству колекції Василя Тарновського. В статье документами Государственного архива Черниговской области освещается страничка истории дома полковой канцелярии и его состояние в конце ХІХ века в связи с передачей Черниговскому губернскому земству коллекции В. В. Тарновского. The article tells about the side of history of the house of regimental chancellery and its
condition at the end of the 19th century in connection with the transmission to Chernihiv’s
Gubernial Zemstvo collection of Vasily Tarnowsky.
In 1896 philanthropist, social and cultural activist, the collector of Ukrainian antiquity
Vasily Tarnovsky enounced a wish to present own unique collection of antiquities to Chernigiv’s
Gubernial Zemstvo. However, presenting a collection to Chernigiv, he put three requisitions, one of which was
a requisition that the collection should be placed in the house of regimental chancellery, or
as specified in the will, in the «ancient house over the Desna». About further negotiations follows the story in this article.